Global Challenges of the Modern Age: Education, Science, Industry - article Editorial (Informaciâ i Innovacii)
On 6 December 2024, ICSTI Headquarters successfully hosted the International Scientific Conference ‘Global Challenges of the Modern Age: Education, Science, Industry’, organized in partnership with the Financial University under the Government of the Russian Federation and the Russian-Italian International University.The conference participants discussed the latest trends in the development of the global economy, prospects for Russia and the world, Russian-Chinese relations as a possible model for countering crisis phenomena, the specifics of digital transformation of agriculture, the role of fintech and other topical issues.The conference was attended by representatives of Russian and foreign universities, young researchers, and members of business communities.